THE EFFECT OF LISTEN-READ-DISCUSS (LRD) TEACHING STRATEGY TO THE READING COMPREHENSION OF GRADE EIGHTH STUDENTS OF SMP NEGERI 2 SIANTAR ON NARRATIVE TEXT - Roza Rapita Soni; Yanti Kristina Sinaga; Asima Rohana Sinaga (CV SWA Anugrah, 2023)
The objective of this research was to find out the effect of Listen-Read-Discuss (LRD) teaching strategy to the reading comprehension of grade eighth students at SMP Negeri 2 Siantar on narrative text. The research design was quantitative research with quasi-experimental design. The sample of this research is 60 eighth grade students of SMP Negeri 2 Siantar selected by purposive sampling. The experimental group was given material using LRD teaching strategy, while the control group was given material with conventional teaching strategy. The data were analyzed using T-test. The research found that the mean of pre-test and post-test in experimental group were 45,33 and 80,33, while the mean of pre-test and post-test in control group were 52,53 and 69,86. The result showed that the students who learned by using LRD teaching strategy had better reading comprehension. After that the researcher found that T-test is higher that T-table (2,247> 1.672) at the level of significance is 5%. It shows that t-test is higher than t-table (2,247 >1.672), Ha is accepted and H0 is rejected. From the analysis of the data, it can be concluded that there is an effect of LRD teaching strategy to the reading comprehension of grade eight students at SMP Negeri 2 Siantar on narrative text.